Research of intellectual capital sourcing at the mechanical engineering enterprises - Осаул, Аліна Олександрівна (Technology audit and production reserves, 2016)
The features of the businesses in mechanical engineering labor market, an impact on the choice of modern management enterprise intellectual capital management strategies are analyzed. It is emphasized that activities trends to attract additional highly qualified engineers are explained by the current state of industrial development and shifting priorities in management strategies based on intellectual resources. Intellectual capital management strategies experience is generalized. The growth, stability and protection strategies are marked out according to the model proposed by Sh. Kohut. Integration policies deemed necessary for engineering companies to develop capital and state policy support. Examples of successful practices of these strategies implementation by engineering companies are proposed. Their decisions were impacted by the present market conditions, demand, supply, market structure, phase of the business cycle. The expediency of apprenticeship practices at the mechanical engineering enterprises is proved. Present day needs of management operating systems in new curriculum of engineers training adjusted for management courses both at local and global levels are illustrated. Externalization of tacit knowledge of enterprise by outsourcing of intellectual capital is identified. The example of externalization is engineering services outsourcing enhancing the competitive position of engineering enterprises in the global economy by minimizing the costs of localization, resources saving, increasing productivity, creating products with high added value. Limitations of outsourcing strategy use caused by key competencies losses of project designers, warranty managements tasks are emphasized.